Economic comparison between conventional aquaponics and FLOCponics systems - Pinho, Sara M. [UNESP]; Flores, Roberto Manolio Valladão; David, Luiz H. [UNESP]; Emerenciano, Maurício G.C.; Quagrainie, Kwamena K.; Portella, Maria Célia [UNESP] (Elsevier, 2022)
Biofloc-based fish production involves a dense microbial co-culture that supports nutrient cycling, generally reducing the amount of feed utilized and the need for mechanic and biological filters. These technical benefits of biofloc technology can lower the costs compared to traditional intensive techniques such as recirculating aquaculture systems (RAS). The RAS is conventionally adopted to integrated fish-plant production in aquaponics systems, and recent studies demonstrated the potential for integrating biofloc technology and hydroponics production in FLOCponics systems. The present study compared the economic viability for integrated agri-aquaculture production of tilapia juveniles and lettuce in FLOCponics (FP) and conventional aquaponics (AP) systems. The study was developed as an investment analysis for the commercial production of tilapia juveniles and lettuce in Brazil under four different scenarios. Two scenarios considered previous experimental results of marketable lettuce in both systems, i.e., 37% of total lettuce production would be marketable in FP (scenario 1) and 98% marketable lettuce in AP (scenario 2). The other two scenarios (using FP and AP systems) considered a hypothetical production in which all the lettuce produced have the marketable quality (scenario 3 and 4, respectively). The economic viability indicators calculated were: Internal Rate of Return (IRR); Net Present Value (NPV); PayBack (PB); Discounted PayBack (DPB); Benefit/Cost ratio (B/C) and Discounted Benefit/Cost ratio (DB/DC). The results showed that the production of Nile tilapia juveniles and lettuce in AP (scenario 2) is profitable, but the 37% marketable lettuce from FP (scenario 1) is not. Both hypothetical scenarios 3 and 4 were identified as profitable. A break-even point was calculated in scenario 1 (FP) to assess the quantities of plants that should be visually suitable for marketing to make such an investment project economically profitable. It was estimated that 68.7% of the lettuces produced should have desirable visual marketable characteristics to make FP feasible. The results show that investing in research to evaluate a multi-cycle production to prove the stability of long-term FLOCponics projects is highly recommended since the financial analysis indicates that FLOCponics could be financially feasible.
Keywords: Agri-aquaculture production; Bioflocs; Break-even point; Investment; tilapia